ANALISIS PRODUKTIVITAS DAN NISBAH KESETARAAN LAHAN KEDELAI–JAGUNG AKIBAT APLIKASI POC AZOLLA PADA BERBAGAI KULTIVAR KEDELAI - Indriana, Kovertina; Komariah, Ai; Noertjahyani; Marina, Ida; Rahma Harti, Adi Oksifa (Journal of Innovation and Research in Agriculture, 2025)
Soybean productivity in Indonesia remains fluctuative and has not yet met national demand, partly due to limited land availability and competition with other crops. Intercropping systems combined with the application of Azolla-based liquid organic fertilizer (LOF) are considered a potential strategy to improve land use efficiency and crop yield. This study aimed to analyze the productivity and Land Equivalent Ratio (LER) of soybean–maize intercropping as affected by Azolla liquid organic fertilizer application on different soybean cultivars. The experiment was conducted in Sanca Village, Gantar District, Indramayu Regency, from July to October 2022 using a non-factorial Randomized Block Design with 30 treatment combinations consisting of six soybean cultivars (Anjasmoro, Dega 1, Deja 2, Dering 1, Gepak Kuning, and Grobogan) and five concentrations of Azolla liquid organic fertilizer (0, 100, 200, 300, and 400 mL L⁻¹), with two replications. Data were analyzed using analysis of variance followed by the Scott–Knott grouping test at the 5% significance level. The results showed that the combination of soybean cultivars and Azolla liquid organic fertilizer significantly affected soybean growth and yield, maize yield, and LER values in the intercropping system. The highest soybean productivity in intercropping was obtained from the Anjasmoro cultivar combined with 400 mL L⁻¹ of Azolla liquid organic fertilizer, while the highest LER value was recorded in the intercropping of maize with the Dering 1 cultivar. All intercropping treatments resulted in LER values greater than 1, indicating that soybean–maize intercropping was more efficient than monoculture systems. Therefore, appropriate selection of soybean cultivars combined with Azolla liquid organic fertilizer application can enhance productivity and land use efficiency in soybean–maize intercropping systems. Supply Chain, Distribution, Efficiency, Technology